What Makes Students Embrace Artificial Intelligence (AI) in Higher Education? Insights from the UTAUT Model - Rafsanjani, Mohamad Arief; Ghofur, Muhammad Abdul; Kamalia, Putri Ulfa; Subroto, Waspodo Tjipto; Srisuk, Prattana (International Journal of Technology and Education Research, 2025)
The rapid advancement of artificial intelligence (AI) has significantly transformed higher education, offering opportunities to enhance learning while simultaneously posing risks of misuse, such as plagiarism and decreased critical thinking skills. This study investigates the determinants influencing students’ adoption and actual use of AI by applying the Unified Theory of Acceptance and Use of Technology (UTAUT). Using a descriptive-explanatory design with an ex post facto approach, data were collected through an online questionnaire distributed to students of the Faculty of Economics and Business, Universitas Negeri Surabaya. A total of 254 responses were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results demonstrate that all four UTAUT constructs—performance expectancy, effort expectancy, social influence, and facilitating conditions significantly affect students’ intention to use AI, with performance expectancy emerging as the strongest predictor. Furthermore, intention to use AI has a substantial direct effect on actual AI usage behavior and mediates the relationship between the four exogenous variables and actual use. These findings indicate that students primarily adopt AI due to its perceived benefits and ease of use, while social and institutional factors play a supporting role. The study highlights the importance of fostering positive behavioral intentions through AI literacy and ethical guidelines to ensure responsible AI integration in higher education. By developing clear institutional policies and providing supportive infrastructures, universities can mitigate the risks of AI misuse while maximizing its potential to improve learning outcomes and uphold academic integrity.